2016
DOI: 10.1002/ar.23355
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and Accommodation of Jaw Adductor Muscles in Canidae

Abstract: The masticatory apparatus amongst closely related carnivoran species raises intriguing questions about the interplay between allometry, function, and phylogeny in defining interspecific variations of cranial morphology. Here we describe the gross structure of the jaw adductor muscles of several species of canid, and then examine how the muscles are scaled across the range of body sizes, phylogenies, and trophic groups. We also consider how the muscles are accommodated on the skull, and how this is influenced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 57 publications
3
28
0
Order By: Relevance
“…Jaw adductor MM scaled isometrically against BM and with slight positive allometry against GM. These results mirror trends seen in the jaw adductors of Felids (Hartstone-Rose et al, 2012) and within Canids (Penrose et al, 2016). Weighted FLs scaled with negative allometry against both size variables, which is also consistent with the results of felid jaw adductor FL.…”
Section: Scaling Of Architectural Properties Within the Musteloideasupporting
confidence: 84%
“…Jaw adductor MM scaled isometrically against BM and with slight positive allometry against GM. These results mirror trends seen in the jaw adductors of Felids (Hartstone-Rose et al, 2012) and within Canids (Penrose et al, 2016). Weighted FLs scaled with negative allometry against both size variables, which is also consistent with the results of felid jaw adductor FL.…”
Section: Scaling Of Architectural Properties Within the Musteloideasupporting
confidence: 84%
“…Details of the muscle dissections can be found in Penrose et al (). In a fox head dissection ( Vulpes vulpes 7), we found that the lateral pterygoid contributed approximately 3% to the overall pterygoid mass (medial pterygoids 8.71 g, lateral pterygoids 0.28 g), and 0.27% to the total jaw adductor muscle mass.…”
Section: Resultsmentioning
confidence: 99%
“…All concur that its role is likely to be insignificant due to its small size and the bony constraints of the TMJ (Hartstone‐Rose, Perry, & Morrow, ; Herring, ; Ström, Holm, Clemensson, Haraldson, & Carlsson, ; Turnbull, ). Further details of the dissection protocol can be found in Penrose et al (Penrose et al, ). The specimen that had undergone MR scanning at both occlusion and wide gape, Vulpes vulpes 6, was also subsequently dissected and photographed at occlusion and wide gape, to confirm the limit of gape ( Vulpes vulpes 6 dissected at wide gape is shown in Figure b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, musteloid estimated bite force scales with positive allometry relative to cranial size, a pattern that is consistent with estimated bite force scaling relative to body mass across all of Carnivora (Christiansen & Wroe, ). Because larger carnivorans exhibit larger jaw adductor muscles that can generate larger bite forces (Hartstone‐Rose et al ., ; Penrose et al ., ), our results suggest that musteloids evolved larger bite forces simply through evolutionary shifts towards larger head and body and head sizes.…”
Section: Discussionmentioning
confidence: 99%